The Structure and Function of Al-Balāghah in Qasidat al-Burda by Imam al-Būṣīrī: A Comparative Analysis - Murdiono; Hadi Nur Taufiq; Saimou Hamissou Malam Mohaman (Universitas Islam Negeri Palopo, 2025)
This study aims to analyze the structure and function of al-balāghah in Qasidat al-Burda by Imam al-Busiri. Through a refined comparative approach, comparing selected verses of al-Burda with stylistic features in classical poetry such as Banat Su‘ad and the works of al-Mutanabbi, the study highlights al-Busiri’s distinct rhetorical identity. Guided by classical balāghah theory—including ʿIlm al-Maʿānī, ʿIlm al-Bayān, and ʿIlm al-Badīʿ—this research examines how rhetorical devices shape meaning and enhance aesthetic effect. Using qualitative textual analysis, fourteen key verses were closely examined to identify major devices such as metaphor, simile, personification, hyperbole, and analogy, and to determine their role in reinforcing thematic unity. Examples from the analysis include the metaphor “Shams al-Dīn” (sun of religion), the hyperbolic expression “Nāzhir al-Badr ghayru nāzhir,” and the personification of the sky in “‘Alāmah al-Samā’ al-Dunyā subḥānahu,” each demonstrating Busiri’s ability to construct vivid spiritual imagery. The findings show that Qasidat al-Burda contains fourteen integrated rhetorical constructions that enrich its spiritual message, elevate the status of the Prophet Muhammad, and refine its aesthetic resonance. These rhetorical strategies not only enhance imagery but also strengthen the poem’s communicative, devotional, and didactic functions. The study concludes that Imam al-Busiri successfully merges artistic expression with religious values, producing a work of enduring influence in both classical Arabic literary heritage and contemporary Islamic scholarship.